Inside Back Cover: Total Synthesis and Biological Assessment of Mandelalide A (Chem. Eur. J. 4/2016). Issue 4 (21st December 2015) - Brütsch, Tobias Michael; Bucher, Pascal; Altmann, Karl‐Heinz
Abstract : The picture shows the marine macrolide mandelalide A together with the starting materials and advanced intermediates that have enabled a highly convergent total synthesis of the macrolactone core of this complex natural product. Like other bioactive macrocycles, mandelalide A is of polyketide origin and it has been described to exhibit antiproliferative activity against some human cancer cell lines, but not others. Here, mandelalide A was found to reduce the proliferation of two lung cancer cell lines with nM potency, but it did not kill all cells even at much higher concentrations. More information can be found in the Full Paper by K.‐H. Altmann et al. onpage 1292 ff.